Expeditious Generation of Biparatopic Common Light Chain Antibodies via Chicken Immunization and Yeast Display Screening - Bogen, Jan P.; Carrara, Stefania C.; Fiebig, David; Grzeschik, Julius; Hock, Björn; Kolmar, Harald (Frontiers in Immunology, 2020)
Bispecific (BsAb) and biparatopic (BpAb) antibodies emerged as promising formats for therapeutic biologics exhibiting tailor-made functional properties. Over recent years, chicken-derived antibodies have gained traction for diagnostic and therapeutic applications due to their broad epitope coverage and convenience of library generation. Here we report the first generation of a biparatopic common light chain (cLC) chicken-derived antibody by an epitope binning-based screening approach using yeast surface display. The resulting monospecific antibodies target conformational epitopes on domain II or III of the epidermal growth factor receptor (EGFR) with lower double- or single-digit nanomolar affinities, respectively. Furthermore, the domain III targeting variant was shown to interfere with epidermal growth factor (EGF) binding. Utilizing the Knob-into-Hole technology (KiH), a biparatopic antibody with subnanomolar affinity was generated that facilitates clustering of soluble and cell-bound EGFR and displayed enhanced antibody-dependent cell-mediated cytotoxicity (ADCC) compared to the parental antibodies. This strategy for generating cLC-based biparatopic antibodies from immunized chickens may pave the way for their further development in therapeutic settings.